the PERAN TEMPAT PEMBUANGAN AKHIR SAMPAH PUUWATU DALAM MENDORONG EKONOMI PEMULUNG MELALUI IMPLEMENTASI EKONOMI SIRKULAR DI KECAMATAN PUUWATU KOTA KENDARI - Ilham Arrahman; Rostin Rostin; Ahmad Ahmad; Wali Aya Rumbia; Syamsir Nur; Tajuddin Tajuddin; Irmawatty Paula Tamburaka (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This research aims to analyze the role of TPAS Puuwatu in implementing circular economy in the waste management system and its contribution to improving the economy of scavengers. The research uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis is carried out interactively through data reduction and data presentation. The informants consist of fifteen people, including formal informants and key informants. The results of the study show that TPAS Puuwatu has transformed into a community-based circular ecosystem through the controlled landfill method. The application of the 3R principle is primarily driven by the role of the scavenger as a "natural filter" that strengthens the initial sorting. However, the implementation of the recovery principle was weakened due to damage to methane gas infrastructure, while redesign and remanufacture were constrained by limited technology and human resources. The economic contribution is seen through an increase in the income of scavengers, with the level of difference influenced by gender.